Assessing the impacts of satellite tagging on growth rates of immature hawksbill turtles - Stokes, Holly J.; Stokes, Kimberley L.; Mortimer, Jeanne A.; Laloë, Jacques‐Olivier; Esteban, Nicole; Hays, Graeme C. (Methods in ecology and evolution, 2025)
Animal‐borne devices including transmitters, data loggers and identification tags are widely used across taxa to address important biological and ecological questions. Some of these devices may affect fitness, hence studies to assess device impacts are important across taxa and developmental stages. We assessed the impact of satellite tagging on sea turtles at a foraging site in the Indian Ocean. Hawksbill turtles (Eretmochelys imbricata) were captured, and satellite tags (Fastloc‐GPS Argos) attached to 25 individuals between 2018 and 2021, with a mean straight carapace length (SCLn‐t) of 55.3 ± 6.9 cm (range = 47.9–69.5 cm; N = 21). We recaptured 12 tagged turtles and removed 11 tags between 2021 and 2023 and estimated growth rates of tagged (N = 10) and untagged (N = 44) animals (mean SCL range = 33.3–69.4 cm) using capture–mark–recapture of 54 individuals at liberty for 730–1095 days. Growth rates decreased exponentially as turtle size increased, and we found no significant difference between tagged and untagged growth rates and body condition. We also found no damage to the carapace from the tag attachment. We suggest that tagging does not impact growth rates at this study site because the turtles (i) typically maintain small home ranges in the lagoon and (ii) are benthic feeders, not actively pursuing prey. We encourage best practice to study the effects of satellite tagging on turtle populations around the world, as the outlook may be different for animals that swim long distances and/or carry large devices.